VERTICAL SEGREGATION IN PRISTIMANTIS SPECIES FROM A BAMBOO FOREST IN SOUTHEAST OF AMAZONIA, BRAZIL - LÓPEZ-ROJAS, Jhon Jairo (2018)
In this work, the vertical stratification in Pristimantis species was studied in a remanescent forest dominated by bamboo in the southwest region of the Amazon. The field work was carried out between December 2012 and May 2013. The differences in height of the perch were analyzed interspecifically, and intraspecific in relation to the structure of the vegetation. A total of four species were recorded, Pristimantis fenestratus being the most abundant and occurring in all sampling units. There was significant interspecific difference in perch height, as well as between adults and juveniles. For P. fenestratus, there was no differentiation of segregation between sampling units. The structure of the vegetation did not explain the preference of heights; however, leaf litter depth influenced its vertical stratification. More data and occurrences are needed in all sampling units to infer better explanations.